Debt Micro-Factor Analysis and How Debt Affects Property Company Value: Case Study Indonesian Property Sector - Aurora, Azril (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The government can provide policies and create economic growth Which conducive, the property sector will be very prospective. The purpose of this study is to obtain empirical evidence and examine the factors that influence policy debt which has implications for the company value of companies listed on the Indonesia Stock Exchange. These factors are Fixed Assets Ratio, Return on Equity, Company Size, Company Growth and Company Age. This research was conducted on companies listed as property companies for the 2010-2015 period on the Indonesia Stock Exchange. Multiple Regression Analysis was used to test the hypothesis and purposive sampling method was used to take the sample. The results showed that the ratio of fixed assets, return on equity, firm size and company growth had no relationship with debt but firm age had a negative relationship with debt and debt did not have implications for firm value partially. On the other hand, all variables have a significant relationship with debt and have implications for company size. The results show an agency problem